BIOKONVERSI BAHAN BERLIGNOSELULOSA MENJADI BIOETANOL MENGGUNAKAN Aspergillus niger DAN Saccharomyces cereviciae - Muhammad Daud; Wasrin Safii; Khaswar Syamsu (Forestry Faculty of Universitas Hasanuddin, 2012)
This study aims to determine the feseability of bioethanol production from lignocellulosic material by using simulataneous saccharification and fermentation (SSF) processes with Aspergillus niger dan Saccharomyces cereviciae. Three different lignocellulosic materials namely sengon wood (Paraserianthes falcataria), gmelina wood (Gmelina arborea), pinus wood and (Pinus merkusii) were pretreated using kraft process to remove lignin content. Then, pulp was treated by using SSF processes. SSF runs were performed in 500 ml fermentors using a total slurry 200 ml. The substrate and nutrient media were autoclaved (121 oC and 20 minutes). The samples diluted to 2.5 % (w v-1) of total slurry was used as substrate. The substrate was added with 10 % (v v-1) A. niger (6.5 x 107 CFU cc-1) of total slurry and then inoculated with 10 % (v v-1) yeast S. cereviciae (1.5 x 109 CFU cc-1). The SSF experiments were run for 96 hours and the data were investigated periodically every 24 hours. The results showed that total of sugar and reducing sugar tended to decrease with time of inoculation whereas ethanol concentration increase significantly. The growth of A. niger and yeast S. cereviciae tended to incease in initial inoculation and decrease by the end of inoculation. The bioethanol concentration on sengon, gmelina, and pinus were 0.53, 0.45 and 0.31 % respectively and produced yields 3.61, 4.60 and 4.16% respectively. Key words: bioethanol, simultaneous saccharification and fermentation, Aspergillus niger, Saccharomyces cereviciae